Health care utilization and survival among patients with AIDS in Belo Horizonte, Minas Gerais, Brazil - Francisco de Assis Acurcio; Cibele Comini Cesar; Mark Drew Crosland Guimarães
A historical cohort study was conducted in three public AIDS referral services in Belo Horizonte, Minas Gerais, to assess the relationship between health care utilization and patient survival following AIDS diagnosis. A review of medical and laboratory records was performed for HIV-infected patients seeking care for the first time in 1989-92. Among 291 patients initially categorized as "A" [asymptomatic, acute HIV, or persistent generalized lymphadenopathy-PGL] or "B" [symptomatic, non-"A", or AIDS-indicator conditions] (CDC, 1992) and who progressed to AIDS, 57.0% died. Mortality rate was 34.9/1.000 person-months. Overall median survival time following AIDS diagnosis was 14.3 months. Multivariate analysis showed that lack of AZT use (RR = 1.87; 95% CI = 1.34-2.61), advanced initial staging (RR = 1.68; 95% CI = 1.20-2.35), 9 or more inpatient days (RR = 1.55; 95% CI = 1.11-2.17), and intervals between outpatient visits longer than 6 months (RR = 0.30; 95% CI = 0.16-0.56) were associated with death. The analysis suggests that: Patients who used health services more often had poorer prognosis; Patients who received AZT survived longer than those who did not; and Variables used to assess health care utilization actually express the end of a process involving seeking and obtaining care.